Model Penyuluhan Sistem Resi Gudang sebagai Upaya Meningkatkan Minat Petani untuk Menjadi Anggota Koperasi Serba Usaha Niaga Mukti Kabupaten Cianjur - Ami Purnamawati; Farahdiba Rifdah Chairani (J-Coop : Journal of Co-operative, 2025)
Koperasi Serba Usaha Niaga Mukti in Cianjur Regency is a multi-purpose cooperative or cooperative that runs three business units, one of which is the warehouse receipt system unit. This unit is the research object as there were the number of farmers unfortunately non- cooperative members use the benefits of warehouse receipt system services. The warehouse receipt system has the potential to increase the existence of cooperatives in increasing the quantity of members through counseling. The aim of this research is to describe the warehouse receipt system extension communication model as an effort to increase farmers to become members of cooperatives, managerial efforts carried out by cooperatives to increase interest among farmers to become members of cooperatives. This research uses approaches to management theory, cooperatives, communication, and extension communication models. The results of this research indicate that the Mukti Commercial Multi-Enterprise Cooperative in Cianjur Regency still needs an ideal extension model to increase interest among farmers in becoming members of the cooperative.